2022
DOI: 10.3390/ijerph19031485
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Perceptions of Harmfulness of Tobacco and Tobacco-like Products in Finland

Abstract: During the recent years, new tobacco and tobacco-like products, e.g., e-cigarettes, have emerged on the market. Adolescents often underestimate health risks in general, including those concerning tobacco. Little is known of adolescents’ perceptions of health risks of the newer products. Our paper compares adolescents’ perceptions of harmfulness of cigarettes, e-cigarettes, snus, water pipes, and nicotine in Finland, a country with a long history of strict tobacco control policy. Online surveys to nationally re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…In this study, improvements in the study outcomes were greatest in terms of sources of snus refusal self-efficacy. Recent studies have shown that adolescents understand the harms of tobacco better than, for example, snus or newer tobacco and nicotine products, such as e-cigarettes or waterpipes ( El-Amin et al, 2022 ; Scheffels et al, 2023 ). Thus, the Fume health game intervention may be more effective with respect to newer tobacco and nicotine products, the harmful health effects of which are less well understood by adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, improvements in the study outcomes were greatest in terms of sources of snus refusal self-efficacy. Recent studies have shown that adolescents understand the harms of tobacco better than, for example, snus or newer tobacco and nicotine products, such as e-cigarettes or waterpipes ( El-Amin et al, 2022 ; Scheffels et al, 2023 ). Thus, the Fume health game intervention may be more effective with respect to newer tobacco and nicotine products, the harmful health effects of which are less well understood by adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the Fume health game intervention may be more effective with respect to newer tobacco and nicotine products, the harmful health effects of which are less well understood by adolescents. At the same time, adolescent experimentation with snus and e-cigarettes is common in the Nordic countries ( Cerrai et al, 2022 ; El-Amin et al, 2022 ; Raitasalo et al, 2022 ). This suggests that there may be a need to further strengthen the health education perspective on newer tobacco and nicotine products in the Fume intervention.…”
Section: Discussionmentioning
confidence: 99%
“…University students are particularly vulnerable to initiating psychoactive substance use, including tobacco, as university represents a transitional phase where social identities are developed and individuals face new challenges and peer pressure [7]. Moreover, many young individuals underestimate the risks associated with tobacco use and perceive themselves as invulnerable to its harms [8]. This phase often marks the transition from experimentation to regular tobacco use, with young adults developing nicotine dependence.…”
Section: Introductionmentioning
confidence: 99%